GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 18 Oct 2019, 01:43 GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  (3x + 2) (2x - 5) = ax² + kx + n . What is the value of a - n + k ?

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

Hide Tags

Math Expert V
Joined: 02 Sep 2009
Posts: 58435
(3x + 2) (2x - 5) = ax² + kx + n . What is the value of a - n + k ?  [#permalink]

Show Tags 00:00

Difficulty:   5% (low)

Question Stats: 87% (01:45) correct 13% (02:07) wrong based on 178 sessions

HideShow timer Statistics

(3x + 2) (2x - 5) = ax^2 + kx + n . What is the value of a - n + k ?

A. 5
B. 8
C. 9
D. 10
E. 11

_________________
Math Expert V
Joined: 02 Aug 2009
Posts: 7977
Re: (3x + 2) (2x - 5) = ax² + kx + n . What is the value of a - n + k ?  [#permalink]

Show Tags

Bunuel wrote:
(3x + 2) (2x - 5) = ax^2 + kx + n . What is the value of a - n + k ?

A. 5
B. 8
C. 9
D. 10
E. 11

Simplify LHS..
$$(3x+2)(2x-5) = 6x^2-11x-10 = ax^2-n+k$$...
equate the coefficients...
a=6 ; k = -11 and n = -10..
so $$a-n+k = 6-(-10)+(-11) = 6+10-11 = 5$$
A
_________________
Intern  Joined: 14 Sep 2015
Posts: 9
Re: (3x + 2) (2x - 5) = ax² + kx + n . What is the value of a - n + k ?  [#permalink]

Show Tags

1
Bunuel wrote:
(3x + 2) (2x - 5) = ax^2 + kx + n . What is the value of a - n + k ?

A. 5
B. 8
C. 9
D. 10
E. 11

Expanding we have 6x^2 - 15x + 4x -10
6x^2 - 11x - 10

Taking coefficients, a = 6, k= -11, n = -10

Therefore a - n + k = 6 - (-10) - 11 = 16 - 11 = 5

The answer is A.
Non-Human User Joined: 09 Sep 2013
Posts: 13241
Re: (3x + 2) (2x - 5) = ax² + kx + n . What is the value of a - n + k ?  [#permalink]

Show Tags

Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________ Re: (3x + 2) (2x - 5) = ax² + kx + n . What is the value of a - n + k ?   [#permalink] 02 Feb 2019, 18:47
Display posts from previous: Sort by

(3x + 2) (2x - 5) = ax² + kx + n . What is the value of a - n + k ?

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne  